VALUE OPTIMIZATION STRATEGY FOR MSME CLUSTERS IN EAST JAVA PROVINCE AFTER THE PANDEMIC - Vita Retyana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to provide a model for developing MSME values in Indonesia based on Geography Spatial Supply Chain 4.0. This model seeks to increase effectiveness by optimizing production factors after the COVID-19 pandemic. This study uses a qualitative method with an exploratory approach in compiling the proposed model for MSME development in Indonesia, especially East Java. The data were obtained from the results of a survey of 800 respondents in East Java province, in-depth interviews with experts, and in-depth observations of existing conditions in the field. This research produces a geographic spatial supply chain model that connects farmers (N-1) to processing industries (N) and end consumers (N+1) through a marketplace that is integrated with local government systems. Marketplace does not only cover software procurement and sales systems, but is broader in marketing, quality control and knowledge transfer. This research contributes to the development of MSMEs in Indonesia, especially in the province of East Java. The research results can be the basis for stakeholder policy making in the development of MSMEs in Indonesia, especially in East Java.